The role of undercooling during clinopyroxene growth in trachybasaltic magmas: Insights on magma decompression and cooling at Mt. Etna volcano. (1st January 2020) - Masotta, M.; Pontesilli, A.; Mollo, S.; Armienti, P.; Ubide, T.; Nazzari, M.; Scarlato, P.
Abstract: Isothermal and undercooling experiments were conducted on one of the most primitive trachybasalts from Mt. Etna volcano in order to examine the crystallization mechanisms controlling the textural and compositional variability of clinopyroxene. Experiments were performed at 400–800 MPa, 1050–1200 °C, 0–4 wt.% H2 O and at oxygen fugacity 2 log units above the Ni-NiO + 2 buffer. In isothermal experiments, the final resting temperature is approached from room temperature and clinopyroxene growth is dominated by an interface-controlled mechanism, leading to the formation of small (∼10 µm) and euhedral crystals with homogeneous compositions. Conversely, in undercooling experiments, the final resting temperature is approached after annealing at temperature above the liquidus, imposing an effective degree undercooling (Δ T ) to the system. In presence of undercooling, the crystallization of clinopyroxene is dominated by a diffusion-controlled mechanism that determines the formation of large (>100 µm) crystals, constituted by two compositionally distinct domains, enriched in Al2 O3  + TiO2 and SiO2  + MgO, respectively. The maximum growth rate ( Gmax ) decreases progressively from ∼10 −7 to ∼10 −8 cm/s as the degree of undercooling increases from ∼20 to ∼230 °C, due to the increase in nucleation rate. At low to moderate degrees of undercooling (Δ T  = 23–41 °C) clinopyroxene is prevalently euhedral to subhedral, whereas at high degrees of undercooling, the crystal shape changes from prevalently subhedral (Δ T  = 73–123 °C) to skeletal and dendritic (Δ T  = 132–233 °C). Hourglass sector zoning similar to that documented for natural phenocrysts from eruptions at Mt. Etna volcano is observed only at low degrees of undercooling (Δ T  = 23–32 °C). This type of zoning develops in the form of the cation exchange [Si + Mg]{-111}  ↔ [Al + Ti]{100} and demonstrates that hourglass sector zoning is an effective indicator of sluggish kinetic effects caused by relatively low degrees of undercooling. In contrast, at increasing degrees of undercooling (Δ T  > 32 °C), strong melt supersaturation determines the early formation of Al2 O3  + TiO2 -rich dendritic crystals and further SiO2  + MgO-rich overgrowths, as the bulk system attempts to return to a near-equilibrium state between the advancing crystal surface and the feeding melt. The experimentally-determined relationship between Δ T and clinopyroxene chemistry is used to reconstruct the crystallization conditions of natural clinopyroxenes from 1974 and 2002–2003 eccentric eruptions at Mt. Etna volcano. Clinopyroxene rims record much higher degrees of undercooling (up to ∼110 °C) than crystal mantles associated with magma recharge at depth (mostly 0–40 °C). Hence, the rims track decompression-induced degassing and cooling during the ascent of magma towards the surface.